Design and Crisis - Gui Bonsiepe (Materia Arquitectura)
This article analyzes aspects of the current crisis in the professional practice of design, its teaching and project discourse. The author criticizes certain design trends, such as self-referentialism, the attempts to turn design into art and the subordination to the one-dimensional criteria of marketing. He also analyzes concepts like “experience design” and “design thinking”. He stresses the implicitly political aspect of Project acting and the difference between design in the Center and in the Periphery, distinguishing a hetero-directed and a self-directed praxis orientated towards strengthening autonomy. Six ways are formulated to come out of the design crisis: relativizing the concept of “market”, recovering common spaces, questioning economist thinking, objecting the development model based on the plundering of resources, liberating teaching from the yoke of mercantilism and reviewing western life style based on a huge consumption of energy and resources.